Pengaruh Earning Per Share, Debt to Equity Ratio, dan Return On Equity terhadap Harga Saham Perusahaan LQ-45 di Bursa Efek Indonesia - Siti Marfuatun; Iin Indarti (Jurnal Ilmiah Aset, 2012)
The purpose of this research was to analyze the influence of earning per share, return on equity and debt to equity ratio to the stock price either partially and simultaneously. This kind of research was correlational. In this research, the population was the letter quality index (LQ 45) companies that go public in Indonesian Stock Exchange from 2007 to 2009, they were 73 companies. The samples were 15 companies. This research used non probability technique in taking sample, determined by purposive sampling specified in judgment sampling. The method of collecting data was literature study and documentation. The technique of data analysis in this research was multiple linier regression. From the research result partially showed that earning per share (t value 3,764 > t table 2,0227) influenced significantly to the stock price. Debt to equityRatio (t value -0,598 < t table 2,0227) and Return on Equity (t value 1,209 < t table 2,0227) didn’t influence significantly to the stock price. While from the research result simultaneously showed that Earning per Share, Debt to Equity Ratio and Return on Equity, significantly influenced the stock price, proved by F value 11,260 > F table 2,85 and influence of 42,3%.